Case Report: A rare RUNX1 rearrangement resulting from t(8;21)(p12;q22) in acute myeloid leukemia with plasmacytoid dendritic cell expansion - Gong, Jinying; Liu, Jialong; Lu, Lisha; Wei, Jiru; Wu, Xue; Zou, Junyan; Feng, Yuan; Zhu, Guoqing; Han, Jing (Frontiers in Oncology, 2025)
In recent years, acute myeloid leukemia with plasmacytoid dendritic cell expansion (pDC-AML) has been recognized as a rare provisional subtype of AML, comprising approximately 3–5% of all reported cases and associated with a poorer clinical outcome compared with non–pDC-AML. Both RUNX1 mutations and rare rearrangements can lead to either complete loss or dominant-negative inhibition of RUNX1 function in pDC-AML, which may play a pivotal role in the aberrant expansion or malignant transformation of plasmacytoid dendritic cells (pDCs). To date, only two cases of pDC-AML with rare RUNX1 rearrangements have been reported. Herein, we reported a rare RUNX1 rearrangement resulting from t(8;21)(p12;q22) in a patient with pDC-AML, leading to the truncated RUNX1 that exhibit structural and functional similarities to RUNX1A and may act as a dominant-inhibitor of wild-type RUNX1. Given the poor prognosis associated with this subtype, CD123-targeted therapy, such as tagraxofusp-erzs, alone or in combination with agents like azacitidine and venetoclax, may represent a rational therapeutic approach. To our knowledge, this represents the third case report of RUNX1 rearrangement in pDC-AML and may provide valuable insights for future research.